Mitochondrial pyruvate carrier in Trypanosoma brucei - Štáfková, Jitka; Mach, Jan; Biran, Marc; Verner, Zdeněk; Bringaud, Frédéric; Tachezy, Jan (Molecular microbiology, 2016)
Pyruvate is a key product of glycolysis that regulates the energy metabolism of cells. In Trypanosoma brucei, the causative agent of sleeping sickness, the fate of pyruvate varies dramatically during the parasite life cycle. In bloodstream forms, pyruvate is mainly excreted, whereas in tsetse fly forms, pyruvate is metabolized in mitochondria yielding additional ATP molecules. The character of the molecular machinery that mediates pyruvate transport across mitochondrial membrane was elusive until the recent discovery of mitochondrial pyruvate carrier (MPC) in yeast and mammals. Here, we characterized pyruvate import into mitochondrion of T. brucei. We identified mpc1 and mpc2 homologs in the T. brucei genome with attributes of MPC protein family and we demonstrated that both proteins are present in the mitochondrial membrane of the parasite. Investigations of mpc1 or mpc2 gene knock-out cells proved that T. brucei MPC1/2 proteins facilitate mitochondrial pyruvate transport. Interestingly, MPC is expressed not only in procyclic trypanosomes with fully activated mitochondria but also in bloodstream trypanosomes in which most of pyruvate is excreted. Moreover, MPC appears to be essential for bloodstream forms, supporting the recently emerging picture that the functions of mitochondria in bloodstream forms are more diverse than it was originally thought.
Keywords: energetický metabolismus; Mitochondria; Cell Line; Monocarboxylic Acid Transporters; mitochondrie; membránové transportní proteiny; mitochondriální membrány; Amino Acid Sequence; Pyruvic Acid; Trypanosoma brucei brucei; Membrane Transport Proteins; přenašeče monokarboxylových kyselin; proteiny přenášející anionty; biologický transport; kyselina pyrohroznová; Energy Metabolism; sekvence aminokyselin; Anion Transport Proteins; buněčné linie; Mitochondrial Membranes; Biological Transport